2016
DOI: 10.1002/jnr.23848
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural and microglial changes after repetitive mild traumatic brain injury in mice

Abstract: Traumatic brain injury (TBI) is a major public health issue, with recent increased awareness of the potential long-term sequelae of repetitive injury. While TBI is common, objective diagnostic tools with sound neurobiological predictors of outcome are lacking. Indeed, such tools could help identify those at risk for more severe outcomes after repetitive injury and improve understanding of biological underpinnings to provide important mechanistic insights. We tested the hypothesis that acute and subacute pathol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
37
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 49 publications
3
37
0
Order By: Relevance
“…74 A recent study of acute repetitive closed head TBI in mice also reported changes in RNA expression indicating activation of microglia in the cortex along with changes in ex vivo DTI AD. 75 Therefore, repetitive concussive or subconcussive impacts may lead to a microglial reaction in the cortex that could be detected noninvasively with continued advances in the clinical application of diffusion imaging approaches. This cortical microglial reaction could have significant functional implications for behavioral deficits and cognitive impairment given the emerging roles of microglia in synaptic pruning and neurodegenerative disease.…”
Section: Discussionmentioning
confidence: 99%
“…74 A recent study of acute repetitive closed head TBI in mice also reported changes in RNA expression indicating activation of microglia in the cortex along with changes in ex vivo DTI AD. 75 Therefore, repetitive concussive or subconcussive impacts may lead to a microglial reaction in the cortex that could be detected noninvasively with continued advances in the clinical application of diffusion imaging approaches. This cortical microglial reaction could have significant functional implications for behavioral deficits and cognitive impairment given the emerging roles of microglia in synaptic pruning and neurodegenerative disease.…”
Section: Discussionmentioning
confidence: 99%
“…Production of inflammatory cytokines is also linked with glial cell activation following injury, and was commonly assessed in these studies. Depending on the cytokine variety, mTBI caused a rapid inflammation response that was shown to peak at 1 (Khuman et al, ), 2 (Namjoshi et al, ), 7 (Robinson et al, ) days post‐impact, with a prolonged sub‐acute profile (Bai et al, ; Mei, Zheng, Tan, Wang, & Situ, ). When chronic time points were assessed, reactive astrocytes and activated microglia persisted, appearing at 6 months (Mannix et al, ) and 3 months (Mannix et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Cellular lysate protein concentrations were determined by Quickstart ™ Bradford protein assay (BioRad, Hercules, CA, USA). Sciatic nerve cytokine expression levels were then determined using a V-PLEX ™ immunoassay (MesoScale Discovery, Gaithersburg, MD, detailed below) panel for identification of the cytokines and chemokines: TNFα, IL-1β, IL-6, IL-10 and CXCL1, as previously validated [63,77]. IL-10 levels in L4-L6 DRGs were also measured using MesoScale Discovery immunoassay platform.…”
Section: Methodsmentioning
confidence: 99%